Answer:
We conclude that the formula to determine the translation of the point to its image will be:
Explanation:
Given
- Original point = A(-1, 4)
- The image of A = A'(3, 3)
In other words:
A (−1, 4) → A' (3, 3)
We need to determine the translation of the point to its image.
It is clear that the coordinates of the image A' (3, 3) of the original point A (−1, 4) can be determined by adding 4 units to the x-coordinate and subtracting 1 unit to the y-coordinate.
Thus, the translation of the point to its image will be:
A (x, y) → A' (x+4, y-1)
Verification
As A(-1, 4), so using the translation formula:
A (x, y) → A' (x+4, y-1)
A (-1, 4) → A' (-1+4, 4-1) = A' (3, 3)
Therefore, we conclude that the formula to determine the translation of the point to its image will be: